Application of a Tetra‐TPD‐Type Hole‐Transporting Material Fused by a Tröger's Base Core in Perovskite Solar Cells. Issue 9 (22nd July 2019) - Braukyla, Titas; Xia, Rui; Malinauskas, Tadas; Daskeviciene, Maryte; Magomedov, Artiom; Kamarauskas, Egidijus; Jankauskas, Vygintas; Fei, Zhaofu; Roldán-Carmona, Cristina; Momblona, Cristina; Nazeeruddin, Mohammad Khaja; Dyson, Paul J.; et al.
Abstract : One of the obstacles to the commercialization of perovskite solar cells (PSCs) is the high price and morphological instability of the most common hole‐transporting material (HTM) Spiro‐OMeTAD. Herein, a novel HTM, termedV1160, based on four N, N ′‐bis(3‐methylphenyl)‐ N, N ′‐diphenylbenzidine (TPD)‐type fragments, fused by a Tröger's base core, is synthesized and successfully applied in PSCs. Investigation of the optical, thermal, and photoelectrical properties shows thatV1160 is a suitable candidate for application as an HTM in PSCs. A promising power conversion efficiency (PCE) of over 18% is demonstrated, which is only slightly lower than that of Spiro‐OMeTAD. Moreover, V1160 ‐based devices exhibit improved performances in dopant‐free configurations and superior stability. Favorable morphological properties in combination with a simple synthesis makeV1160 and related materials promising for HTM applications. Abstract : A hole‐transporting material (HTM), termedV1160, based on four TPD‐type fragments connected by a Tröger's base structural core, is synthesized, characterized, and applied as an HTM in perovskite solar cells. Demonstrating an over 18% power conversion efficiency, the fully amorphous nature ofV1160, suggesting further studies in TPD‐based materials, is warranted.